سياسة التيسير الكمي كأسلوب حديث لإدارة السياسة النقدية في ظل الأزمات: تجربة كل من اليابان والولايات المتحدة الأمريكية - مطاي, عبد القادر; راشدي, فتيحة (جامعة الوادي University of Eloued, 2016)
نحاول من خلال هذه الورقة البحثية تسليط الضوء على أحد أهم السياسات التي تستخدمها الدول للقضاء على ظاهرة الانكماش التي تسود اقتصادياتها ألا و هي سياسة التيسير الكمي التي تعتبر أداة غير تقليدية للسياسة النقدية ، حيث يقوم البنك المركزي بموجبها بإصدار النقود وشراء السندات الحكومية بهدف تخفيض معدل الفائدة وزيادة السيولة في الاقتصاد ، وهذا بهدف التأثير على الاقتصاد الحقيقي والمالي بواسطة مجموعة من القنوات . إن تطبيق سياسة التيسير الكمي يكون أساسا حسب حالة اقتصاد البلد ، علما أم اليابان كانت السباقة في تطبيقها سنة 1999 و انتشر تطبيقها في مختلف بلدان العالم كالولايات المتحدة الأمريكية و دول الإتحاد الأوروبي و حتى بعض الدول العربية إثر أزمة الرهن العقاري 2008 التي هزت الإقتصاد العالمي . we are trying through this paper highlight one of the most important policies used by countries to eliminate the phenomenon of deflation, which dominates their economies, that is quantitative easing policy, which is a tool unconventional monetary policy, where the central bank which issued coins and buy government bonds in order to reduce interest rate and increased liquidity in the economy, and this is the aim of influencing the real and the financial economy through a variety of channels. The application of the quantitative easing policy is mainly depending on the status of the country's economy, note or Japan was the first to be applied in 1999 and spread application in different countries of the world like the United States of America and the Aruban Union and countries, even some Arab states following the mortgage the 2008 crisis that shook the global economy.
Quantitative easing policy as a way to manage a modern monetary policy  in times of crisis -free Trial would both Japan and the United States, USA
مقال- مجلة رؤى اقتصادية
Keywords: سياسة التيسير الكمي ، السياسة النقدية ، الازمات; quantitative easing policy, monetary policy, crises